: asked on dontworry48
05.12.2021

# Prove that each of the expressions below are equivalent by evaluating the expressions given. Given g = 3. 15g-2(2g+6) and 11g-12

0

24.06.2023, solved by verified expert
Unlock the full answer

Answer with Step-by-step explanation:

We are given that

g=3

and

We have to prove that two expressions are equivalent by evaluating the expressions given

Substitute the value of g in the given expression

Substitute the value of g in the given expression

Hence,

15g-2(2g+6) = 11g-12 when g=3

It is was helpful?

### Faq

Mathematics
P Answered by Master

21 for both expressions

Step-by-step explanation:

Mathematics
P Answered by Specialist

21 for both expressions

Step-by-step explanation:

Mathematics
P Answered by PhD

Answer with Step-by-step explanation:

We are given that

g=3

and

We have to prove that two expressions are equivalent by evaluating the expressions given

Substitute the value of g in the given expression

Substitute the value of g in the given expression

Hence,

15g-2(2g+6) = 11g-12 when g=3

Mathematics
P Answered by PhD

a. substitute 2 into each expression, and evaluate them

Step-by-step explanation:

Mathematics
P Answered by PhD

a. substitute 2 into each expression, and evaluate them

Step-by-step explanation:

Mathematics
P Answered by PhD

SI=(P*R*T)/100

P=2000

R=1.5

T=6

SI=(2000*1.5*6)/100

=(2000*9)/100

=180

Neil will earn interest of 180

Mathematics
P Answered by PhD
Answer: 440 grams for 1.54 is the better value
Explanation:
Take the price and divide by the number of grams
1.54 / 440 =0.0035 per gram
1.26 / 340 =0.003705882 per gram
0.0035 per gram < 0.003705882 per gram
Mathematics
P Answered by PhD

For 1 flavor there are 9 topping

Therefore, for 5 different flavors there will be 5*9 choices

No of choices= 5*9

=45

Mathematics
P Answered by PhD

The answer is in the image

Mathematics